Assessment of the Pharmacological Activities of Ardisia solanacea Roxb: An Ethnomedicinal Plant used in Bangladesh - Mohammad Rashedul Islam; Nawreen Monir Proma; Jannatul Naima; Md. Giash Uddin; Syeda Rubaiya Afrin; Mohammed Kamrul Hossain (Journal of Pharmacy and Nutrition Sciences, 2020)
Objective: This study aims to uncover the anti-diarrheal, antioxidant, thrombolytic, and anthelmintic activities of methanol extract of A. solanacea (ASME) and its soluble n-hexane fraction in methanol (ASNH). Materials and Methods: The phytochemical assessment of this plant was performed by using the standard method. The anti-diarrheal property was screened by castor oil induced diarrhea in Swiss albino mice and plant extract was administered into mice by oral gavage. The antioxidant property was being investigated by two different in vitro methods such as ferric reducing effect assay and superoxide scavenging activity assay. The thrombolytic activity was evaluated by in vitro clot lysis procedure, and the anthelmintic study was carried out on earthworm Pheretima posthuma. Results: In castor-oil induced diarrhea, ASME and ASNH induced a significant decrease (**P<0.005) in the total number of defecation within 4 hours of the testing period (200 and 400 mg/kg) when compared to the standard drug loperamide. During the evaluation of the antioxidant property, ASME showed promising reducing power with an IC50 value of 79.14 µg/mL when compared to the standard ascorbic acid in ferric reducing effect assay. After that, ASME displayed significant scavenging effect with the IC50 value of 154.36 µg/mL when compared to standard curcumin in superoxide scavenging activity assay. In the thrombolytic activity, different doses of ASME and ASNH were used. These extracts produced considerable clot lysis of human blood, showed significant (P<0.001) result in a concentration dependent manner. The crude ASME displayed anthelmintic activity in adult earth worm in a dose-dependent manner. Conclusion: It can conclude that compared to standard drugs, A. solanacea have potential anti-diarrheal, antioxidant, thrombolytic, and anthelmintic activity.